Comparison of induction of spinal anesthesia in sitting position with legs parallel and crossed for cesarean section: A randomized controlled trial - Nitu Puthenveettil; Sajan Rahman; Arun Ramayyan Achary; Sobha Nair; Dilesh Kadapamannil; Jerry Paul (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: The position of the patient during subarachnoid block has a role in its success. Landmarks of the spine can be easily identified in sitting position. Sitting position with legs parallel (LPSP) produces a reversal of lumbar lordosis. The crossed-leg sitting position (CLSP) is an alternative position. In this study, we compared the ease of performing subarachnoid blocks in these two positions. The objectives were to compare the attempts at subarachnoid placement, patient comfort, ease of landmark palpation, level of block, hypotension, and neonatal outcomes. Material and Methods: This randomized trial was performed in 80 parturients posted for elective cesarean section. Parturients were assigned randomly to two groups. In group LPSP, the subarachnoid block was performed in sitting position with legs parallel and in group CLSP in the CLSP with knees and hips flexed. Results: The percentage of parturients with a successful subarachnoid block in the first attempt was higher in the CLSP than in LPSP group (87.5% versus 55%). The remaining 12.5% parturients in the CLSP group had successful block in the second attempt. In the LPSP group, 32.5% required two attempts and 12.5% required more than two attempts. This difference was statistically significant (P-value of 0.003). The landmark was easily palpable in 92.5 versus 67.5% of parturients in CLSP and LPSP, respectively, with a P-value of 0.014. Conclusion: CLSP is better than a sitting position with legs parallel for reducing the number of attempts and improving the ease of performing the subarachnoid block.